Integrative Roles of Phytohormones on Cell Proliferation, Elongation and Differentiation in the Arabidopsis thaliana Primary Root - Zluhan-Martínez, Estephania; López-Ruíz, Brenda Anabel; García-Gómez, Mónica L.; García-Ponce, Berenice; de la Paz Sánchez, María; Álvarez-Buylla, Elena R.; Garay-Arroyo, Adriana (Frontiers in Plant Science, 2021)
The growth of multicellular organisms relies on cell proliferation, elongation and differentiation that are tightly regulated throughout development by internal and external stimuli. The plasticity of a growth response largely depends on the capacity of the organism to adjust the ratio between cell proliferation and cell differentiation. The primary root of Arabidopsis thaliana offers many advantages toward understanding growth homeostasis as root cells are continuously produced and move from cell proliferation to elongation and differentiation that are processes spatially separated and could be studied along the longitudinal axis. Hormones fine tune plant growth responses and a huge amount of information has been recently generated on the role of these compounds in Arabidopsis primary root development. In this review, we summarized the participation of nine hormones in the regulation of the different zones and domains of the Arabidopsis primary root. In some cases, we found synergism between hormones that function either positively or negatively in proliferation, elongation or differentiation. Intriguingly, there are other cases where the interaction between hormones exhibits unexpected results. Future analysis on the molecular mechanisms underlying crosstalk hormone action in specific zones and domains will unravel their coordination over PR development.